The Role of ESG in Credit Decision-Making: A Case Study of Bank Negara Indonesia (BNI) Based on Sustainability Reports 2021–2024 - Steelyana W, Evy; Christy, Audilia; Abhinaiya, Ananda Marshall; Ramadhanti, Kanisa Alexandra; Saskia, Adiva Putri; Widyaningrum, Widyaningrum; Safina, Ayisha Nur (The Eastasouth Management and Business, 2026)
This study aims to analyze the implementation of Environmental, Social, and Governance (ESG) principles as a basis for credit decision-making at Bank Negara Indonesia (BNI), based on its Sustainability Reports for the 2021–2024 period. The research is motivated by the growing demand for banks to integrate sustainability considerations into lending decisions, driven by strengthened sustainable finance regulations and increasing environmental, social, and governance risks. This study adopts a descriptive qualitative approach using a literature review and case study method. The data are derived from BNI’s Sustainability Reports (2021–2024), relevant international academic journals on ESG and banking, and regulatory documents issued by the Financial Services Authority (OJK). Data analysis is conducted through content and comparative analysis to assess the alignment between BNI’s ESG practices and empirical findings in the literature. The results indicate that ESG implementation at BNI has evolved progressively, from a credit risk mitigation instrument in 2021, to a debtor selection and incentive mechanism in 2022, further integrated into Risk Acceptance Criteria and climate risk stress testing in 2023, and ultimately embedded as part of a sustainable credit strategy in 2024. These findings suggest that ESG has functioned as a strategic governance instrument influencing credit allocation and portfolio quality. This study concludes that the integration of ESG as a basis for credit decisions contributes to portfolio stability, institutional reputation, and BNI’s alignment with sustainable development objectives.